PHILOSOPHICAL COMPARATIVISTICS IN THE CONTEXT OF PROBLEMS OF DIALOGUE OF CULTURES OF THE ANCIENT WORLD (Scientific journal of the Fergana State University, 2023)
Ancient Eastern and Western philosophy is the prelude to scientific and spiritual development of mankind. Regardless of the uniqueness of their development, they have some common laws. Philosophical comparativism, as a field of historical-philosophical research, compares the various levels of the hierarchy of Western and Eastern philosophical heritage. Philosophical comparativism leads to new historical and philosophical paradigms and defines new directions for considering the modern historical process.In this article, the interaction of the ancient Western and Eastern cultures is highlighted, views on historical-philosophical processes, the history of philosophy as a dialogue of philosophical cultures are studied.